Docosahexaenoic Acid Supplemented Diet Influences the Orchidectomy-Induced Vascular Dysfunction in Rat Mesenteric Arteries - Villalpando, Diva M.; Navarro, Rocío; del Campo, Lara; Largo, Carlota; Muñoz, David; Tabernero, María; Baeza, Ramiro; Otero, Cristina; García, Hugo S.; Ferrer, Mercedes (PLOS ONE, 2017)
Over the past few decades, the cardiovascular benefits of a high dietary intake of long-chain polyunsaturated fatty acids (PUFAs), like docosahexaenoic acid (DHA), have been extensively studied. However, many of the molecular mechanisms and effects exerted by PUFAs have yet to be well explained. The lack of sex hormones alters vascular tone, and we have described that a DHA-supplemented diet to orchidectomized rats improve vascular function of the aorta. Based on these data and since the mesenteric artery importantly controls the systemic vascular resistance, the objective of this study was to analyze the effect of a DHA-supplemented diet on the mesenteric vascular function from orchidectomized rats. For this purpose mesenteric artery segments obtained from control, orchidectomized or orchidectomized plus DHA-supplemented diet were utilized to analyze: (1) the release of prostanoids, (2) formation of NO and ROS, (3) the vasodilator response to acetylcholine (ACh), as well as the involvement of prostanoids and NO in this response, and (4) the vasoconstrictor response to electrical field stimulation (EFS), analyzing also the effect of exogenous noradrenaline (NA), and the NO donor, sodium nitroprusside (SNP). The results demonstrate beneficial effects of DHA on the vascular function in orchidectomized rats, which include a decrease in the prostanoids release and superoxide formation that were previously augmented by orchidectomy. Additionally, there was an increase in endothelial NO formation and the response to ACh, in which NO involvement and the participation of vasodilator prostanoids were increased. DHA also reversed the decrease in EFS-induced response caused by orchidectomy. All of these findings suggest beneficial effects of DHA on vascular function by reversing the neurogenic response and the endothelial dysfunction caused by orchidectomy.